Screening for psychological distress in very long-term adult survivors of childhood cancer. (3rd July 2016) - de Laage, Astrid; Allodji, Rodrigue; Dauchy, Sarah; Rivollet, Sophie; Fayech, Chiraz; Fresneau, Brice; Oberlin, Odile
ABSTRACT: This study evaluated the prevalence of psychological distress (PD) in a cohort of 348 adult childhood cancer survivors with a very long-term follow-up and assessed the characteristics associated with this distress (cancer type, treatment, sex, age at diagnosis, self-reported late effects, social support, type of remembrance, time since the diagnosis, age at evaluation), assuming that with time since the diagnosis, the PD of survivors will approximate that of the general population. Before attending a long-term follow-up consultation, survivors were sent 3 questionnaires: the Brief Symptom Inventory-18, the Impact of Event Scale, and the Illness Worry Scale (IWS). During the visit, they were administered the Mini-International Neuropsychiatric Interview (MINI) by a psychologist. The mean age of the survivors was 38.5 years (18.1–65.8) at consultation, 7 years (0.0–18.0) at cancer diagnosis, and mean time since diagnosis was 31.5 years (8.8–56.1). Multiple regression analyses of the data collected from self-administered questionnaires confirmed that being female, living alone, and self-reported late effects were associated with the high scores for all scales. Negative remembrances and being accompanied to the clinic were associated with higher IWS scores. Unlike the initial hypothesis, the MINI showed that, compared with controls, survivors experienced a higher prevalence of anxiety and mood disorders even after a very long time since the diagnosis. These findings show that a substantial subset of survivors experiment a high prevalence of PD, higher than the general population, and should be screened for PD whatever the time since the diagnosis.